Androgenic hormone profile in patients with androgenetic alopecia - I. N. Konrakhina; A. N. Mareeva; P. A. Kalinina; M. G. Abuladze (Vestnik Dermatologii i Venerologii, 2017)
In this article, the outcomes of the range of researches are described including the data on levels of testosterone, dihydrotestosterone, dehydroepiandrosterone sulfate, sex hormone-binding globulin and other components of androgen hormone profile in issues and biological fluids of males with androgenetic alopecia. Besides, in this article we describe results of recent studies devoted to effects of androgens on hair follicles and the role of 5-alpha reductase in conversion of androgens.